ISG15 and ISGylation in Human Diseases - Oygul Mirzalieva; Meredith Juncker; Joshua Schwartzenburg; Shyamal Desai (Cells, 2022)
Type I Interferons (IFNs) induce the expression of >500 genes, which are collectively called ISGs (IFN-stimulated genes). One of the earliest ISGs induced by IFNs is ISG15 (Interferon-Stimulated Gene 15). Free ISG15 protein synthesized from the ISG15 gene is post-translationally conjugated to cellular proteins and is also secreted by cells into the extracellular milieu. ISG15 comprises two ubiquitin-like domains (UBL1 and UBL2), each of which bears a striking similarity to ubiquitin, accounting for its earlier name ubiquitin cross-reactive protein (UCRP). Like ubiquitin, ISG15 harbors a characteristic β-grasp fold in both UBL domains. UBL2 domain has a conserved C-terminal Gly-Gly motif through which cellular proteins are appended via an enzymatic cascade similar to ubiquitylation called ISGylation. ISG15 protein is minimally expressed under physiological conditions. However, its IFN-dependent expression is aberrantly elevated or compromised in various human diseases, including multiple types of cancer, neurodegenerative disorders (Ataxia Telangiectasia and Amyotrophic Lateral Sclerosis), inflammatory diseases (Mendelian Susceptibility to Mycobacterial Disease (MSMD), bacteriopathy and viropathy), and in the lumbar spinal cords of veterans exposed to Traumatic Brain Injury (TBI). ISG15 and ISGylation have both inhibitory and/or stimulatory roles in the etiology and pathogenesis of human diseases. Thus, ISG15 is considered a “double-edged sword” for human diseases in which its expression is elevated. Because of the roles of ISG15 and ISGylation in cancer cell proliferation, migration, and metastasis, conferring anti-cancer drug sensitivity to tumor cells, and its elevated expression in cancer, neurodegenerative disorders, and veterans exposed to TBI, both ISG15 and ISGylation are now considered diagnostic/prognostic biomarkers and therapeutic targets for these ailments. In the current review, we shall cover the exciting journey of ISG15, spanning three decades from the bench to the bedside.